Exposición al ruido por tráfico vehicular y su impacto sobre la calidad del sueño y el rendimiento en habitantes de zonas urbanas - Zamorano González, Benito; Velázquez Narváez, Yolanda; Peña Cárdenas, Fabiola; Ruiz Ramos, Lucía; Monreal Aranda, Óscar; Parra Sierra, Víctor; Vargas Martínez, José Ignacio (El Colegio de México A.C., 2019)
The objectives of the study are: 1) to determine the level of noise generated by motor vehicles, at the city of Matamoros, Tamaulipas, and 2) to identify the impact of environmental noise on sleep quality and performance of the inhabitants of the urban area. The study was quantitative, transversal and correlational. Noise was measured in seven crossings, and for the collection of data on the quality of sleep and performance; the size of shows was of 732 participants. It was concluded that traffic noise is associated with the subjective sleep quality, which is significantly related to the performance.